Why should the men who have sex with men population in India be vigilant for monkeypox infection? - Elangovan Arumugam; Santhakumar Aridoss; Nagaraj Jaganathasamy; Malathi Mathiyazhakan; Rajat Shurva Adhikary; Manoj V Murhekar (Wolters Kluwer Medknow Publications, 2023)
Monkeypox (MPX) is a zoonotic infection caused by the monkeypox virus (MPXV) and is primarily characterized by rash or pox marks and lymph node enlargement. The recent MPX has quickly spread across the globe and is now declared a global public health emergency. Being a contact illness, sexual encounters have been identified as the most common mode of transmission in the 2022 multicountry MPX outbreak. Data suggest that MPX is highly concentrated in men who have sex with men (MSM) networks and among those who had a recent sexual encounter with one or more partners. In India, the estimated MSM population was 569,346 in 2019. An analysis of the sexual partnerships among MSM suggests a potential highly interconnected MSM network in India, increasing the risk of MPX burden. The viewpoint emphasizes the need for community-level awareness and surveillance for the early detection and prevention of MPX infection in India.